Zapa Spices / Izzaty Nabila Arisya Suhaimi ... [et al.] - Suhaimi, Izzaty Nabila Arisya; Mohamad Juadzil, Nur Shaerah; Syamsul, Nur Suhana; Shaari, Nurul Najwa; Joseph, Stella; Karim, Syakirah (2021)
In this case study, we conduct an interview with a business owner who owns her own brand and a factory. From a chemistry teacher to a business owner, that is how the founder of Zapa Spices Madam Paizah Shaharudin upgraded her life and found what she wants and loves to do. Starting only from her bad experience in cooking, it does not become a hindrance for her but instead she challenges herself to create a product that could help people like her and that is how Zapa Spices was born. It took her many challenges and steps to reach what she had today. In this report, we will dissect little by little on Zapa Spices’ business and uncover the successes and weaknesses; high and low in the business that they have faced. Zapa Spices is managed by the founder herself, Madam Paizah Shaharudin who is also the marketer for this company, helped by the co-manager who is also the accountant for the company; Mr. Mohd Norzaidee Muhammad. The company started with only 5 main products such as shallot powder and garlic powder; and now it grows to almost 27 kinds of product. The products are available through stockists, agents, and dropshippers around Malaysia and currently they already have 7 stockists in the country. The products are also available in hypermarkets which are Family Store and Halal Mart. Zapa Spices business and marketing strategies are more focused on the promotion of the products. The company used social media such as Facebook, Instagram, and TikTok to gain followers and create brand awareness. Although Zapa Spices only started the business for around 6 years, they managed to achieve profit per year from only RM3000 in 2016 to RM350,000 in 2019; a hundred times more only after 3 years of their start-up. This financial achievement shows the capabilities that Zapa Spices have and how this business has their own strengths. Based on the interview organized with the Zapa Spices’ founder, we managed to make a SWOT analysis about the business. The business utmost strength is on the products produced which are in high demand as it is easy to use for cooking. However, with increased demand, their weakness would come forward as the company is lacking in processing machines. The company is also threatened by some uncertain conditions such as staff error and the inconsistent raw material prices. In addition, Zapa Spices have a really big opportunity to expand their business and penetrate the international market as products produced by Zapa Spices are really in high demand by people who live overseas, especially Malaysian who want some Asian ingredients in their cooking.